Evaluating nest supplementation as a recovery strategy for the endangered rodents of the Florida Keys. Issue 2 (13th August 2016) - Cove, Michael V.; Simons, Theodore R.; Gardner, Beth; Maurer, Andrew S.; O'Connell, Allan F.
Abstract : The Key Largo woodrat ( Neotoma floridana smalli ) and Key Largo cotton mouse ( Peromyscus gossypinus allapaticola ) are federally endangered subspecies endemic to the tropical hardwood hammocks of Key Largo, Florida. Woodrats are considered generalists in habitat and diet, yet a steady decline in natural stick nests and capture rates over the past several decades suggests that they are limited by the availability of nesting habitat due to habitat loss and fragmentation. The more specialized Key Largo cotton mouse appears to rely on old growth hammock, a habitat type that is rare following past land clearing. In 2004, the U.S. Fish and Wildlife Service started building supplemental nest structures to restore habitat quality and connectivity for these endangered rodents, but nest use requires evaluation. We used camera traps and occupancy models to evaluate the factors influencing woodrat and cotton mouse use of the supplemental nests. We detected woodrats at 65 and cotton mice at 175 of 284 sampled nest structures, with co‐occurrence at 38 nests. Woodrat nest use followed a gradient from low nest use in the north to high nest use in the south, which might relate to the proximity of free‐ranging domestic cat ( Felis catus ) colonies in residential developments. Cotton mouse nest use, however, was related positively to mature hammock and related negatively to disturbed areas (e.g. scarified lands). The two species occurred independently of each other. Stick‐stacking behavior was observed at supplemental nests and, although it was correlated with detection of woodrats, it was not a strong predictor of their occurrence. We suggest that nest supplementation can be an important tool for species recovery as habitat quality continues to improve with succession.